Approach Developed According to Sustainable Development Goals and Challenges for Future Professionals in Social Intervention - Eva Maria Picado-Valverde; Amaia Yurrebaso; Raquel Guzmán-Ordaz; Ana Belén Nieto-Librero; Nerea Gonzalez-García (Social Sciences, 2022)
In 2015, the United Nations and various countries committed to achieving the Sustainable Development Goals. The 17 goals revolve around 3 main axes: eradicating poverty, protecting the planet, and ensuring peace and prosperity for all people by 2030. These goals are integrated so that interventions in one area inevitably affect the others. Undoubtedly, this application involves developing competencies related to Prejudice, conflict resolution, and empowerment. Our research aims to analyse the knowledge and competency of university students undergoing specific training to facilitate the application of UNESCO’s objectives in their work performance, while incorporating human rights as a basis for all future actions. A total of 241 students from the University of Salamanca participated. The average age of the sample was 21.13 years; 76.8% were female, and 23.2% were male (22.41 ± 7.17 years old). The data collection protocol included questions related to knowledge of the Sustainable Development Goals and involving SDGs in their personal life and future profession, which were assessed using the empowerment Scale, the Conflictalk Scale, and the Subtle and Overt Bias Scale. Significant differences were found between SDGs knowledge and involvement with academic courses. There was a direct relationship between this knowledge and involvement with the control, esteem, and activism dimensions of the Empowerment Scale, cooperative from the Conflictalk Scale, and positive emotions had inverse relationships with threat–rejection, and traditional values from the prejudice scale. Our study found that students who are more engaged with the SDGs resolve conflicts cooperatively, foster community activism, and experience positive emotions, whereas students with aggressive conflict resolution are more Prejudiced.